(3GdHQgGf Ydi Yed eMeO Hf GdUHGM aj EeJMGf GdTeSs - (3efUhQ Hf Ydj Hf YQGb, CHh fUQ,J (B425 (3g` s
(3ChdgG (B:s
(3JCedJ (B- (3CjOc Gddg (B- (3QSGdI eMeO Hf GdUHGM ai EeJMGf ehVY GdTeS hejdgG hSYI eTQbgG hcejI eSjQgG , hCJjJ ai EUdGMgG hEbGeI GdHQgGf Ydi eG CUdMJg efgG s
(3BNQgG (B:s
(3aCeG GdWQjb Edi JMbjb Pdc HZGjI eGai hSY GdHTQ , abO edFJ Hg cJH CaGVd gPg GdUfGYI hJVef cJGHfG GdehShe HGdeLSWi GdTGgi ef Pdc eeG gh eNUhU HfG , eGajg caGjI hHdGZ JeJ GdQSGdI hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B93(3X (B- (3U(B96(3Xs
(3HgG fXGe GdJYbjHIs
(3HgG CTcGd gfOSjIs
(3QSGdI HYK HgG Edi CHj GdQjMGf eMeO Hf CMeO GdHjQhfi GdeJhai SfI (B440s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs